Environmental impact of a tele-screening program for diabetic retinopathy in rural Argentina - Ortiz Basso, Tomas (2024)
Background: Tele-screening programs for diabetic retinopathy are implemented worldwide, but the environmental impact has not been studied yet. The aim of this study was to evaluate the emission reduction achieved by a tele-screening program for diabetic retinopathy in La Pampa (Argentina). Methods: A descriptive study was performed comparing the emissions generated with and without the program. A retinal camera was transported to 60 rural cities, and the images were classified asynchronously as “referable” and “non-referable”. An ophthalmologist then traveled to each location to assess the identified “referable” cases. The eqCO2 emissions generated by the program were compared with those that patients would have generated if they had traveled from their location to the nearest ophthalmology center in the conventional manner. Results: Emissions generated per patient without the program were equivalent to 63 kg, whereas with program implementation they ranged from 4 kg to 18 kg. The reduction in emissions per patient for 2019, 2020, and 2021 was 45 kg, 41 kg, and 62 kg, respectively. The absolute reduction in eqCO2 emissions by the program for 2019, 2020, and 2021 was 166Tn, 28Tn, and 161Tn, respectively. Conclusion: CO2 emissions were significantly reduced by the tele-screening program for diabetic retinopathy prevention in La Pampa. Ophthalmologists should consider the environmental impact when implementing their practice.